IFPRI Malawi monthly maize market report, June 2020 - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
The average retail price of maize fell marginally by 0.4 percent in the second week of June but remained stable at MWK 174/kg in subsequent weeks. This price is 3.6 percent higher than in May and 5 percent higher than in June 2019. A slight rise in prices is anticipated as the main harvest season is coming to an end in most districts.